2018
DOI: 10.1016/j.actbio.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

RNA interfering molecule delivery from in situ forming biodegradable hydrogels for enhancement of bone formation in rat calvarial bone defects

Abstract: Delivery of RNAi molecules may be a valuable strategy to guide cell behavior for tissue engineering applications, but to date there have been no reports of a biomaterial system capable of both encapsulation of cells and controlled delivery of incorporated RNA. Here, we present PEG hydrogels that form in situ via Michael type reaction, and that permit encapsulation of hMSCs and the concomitant controlled delivery of siNoggin and/or miRNA-20a. These RNAs were chosen to suppress noggin, a BMP-2 antagonist, and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 67 publications
2
73
0
Order By: Relevance
“…[11,12] Although nanoparticles have been utilized to deliver miRs, [13,14] repeated administrations were almost always required to achieve long-term gene silencing in vivo. [16][17][18] However, hydrogels are often isotropic in architecture and hence lack the ability to direct tissue regrowth. [16][17][18] However, hydrogels are often isotropic in architecture and hence lack the ability to direct tissue regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Although nanoparticles have been utilized to deliver miRs, [13,14] repeated administrations were almost always required to achieve long-term gene silencing in vivo. [16][17][18] However, hydrogels are often isotropic in architecture and hence lack the ability to direct tissue regrowth. [16][17][18] However, hydrogels are often isotropic in architecture and hence lack the ability to direct tissue regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that miR-100-5p and miR-143-3p can promote MSC osteogenesis, but the future applicability of this approach was limited by the complexity of the system which required multiple stages of manipulation to transfect and then encapsulate the cells. In recent years, a handful of studies have probed the use of in situ hydrogel transfections for therapeutic application ranging from siRNA delivery in vitro to miRNA delivery in vivo [21,24,25,26,6,27]. Interestingly however, these studies are limited to the use of either a single transfection agent or a limited range in mechanical properties for the base hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels are polymer networks with hydrophilic properties. Researchers have demonstrated that PEGylation hydrogels constantly release siRNA against noggin and miRNA-20a mimics and promote encapsulated human bone marrow-derived mesenchymal stem cells (hMSCs) to differentiate into osteoblasts [116]. In another study, scientists from the Massachusetts Institute of Technology (MIT) showed that a novel self-assembled dual-color RNA-triple-helix hydrogel composed of miRNA-225 mimics and miRNA-221 antagomirs facilitated nearly 90% tumor shrinkage in a triple-negative breast cancer mouse model [117].…”
Section: D Scaffold-based Delivery Systemsmentioning
confidence: 99%